Organizational Culture and Work Discipline and Their Effect on Employee Performance - Calen; Santi Nururly; Injen Pardamean Butarbutar; Sudung Simatupang; Marto Silalahi (International Journal of Social Science and Business, 2022)
Today the success of an organization cannot be separated from the ability of members to be involved in the management of every component of the organization. This ability can be successful when the performance of members of the organization can be achieved. Many factors can support the success of this performance. Every organization has an organizational culture and work discipline that is expected to support the organization in improving employee performance. This study aimed to determine the effect of corporate culture and work discipline on employee performance. This research was conducted at the Regional Tax and Levy Management Agency Technical Implementation Unit (UPT) of SAMSAT Pematangsiantar, totaling 43 employees. The analysis results found that the variables of organizational culture, work discipline, and employee performance have valid and reliable criteria and have average distribution results. Then corporate culture and work discipline can explain employee performance variables by 54% with a substantial correlation coefficient value. The results of the hypothesis found that organizational culture and work discipline have a partial influence on employee performance; for the simultaneous test results that corporate culture and work discipline have a positive and significant impact on employee performance, the results of the greatest influence on work discipline variables. This indicates that work discipline is the most critical factor in supporting employee performance.